2018
DOI: 10.1002/pen.24985
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory epoxy nanocomposites with carbonaceous fillers and in‐situ generated silver nanoparticles

Abstract: Aim of this work is to develop a novel epoxy based nanocomposite and to analyse its shape memory behavior. In particular, silver nanoparticles are in‐situ generated within an epoxy resin subsequently filled with both carbon black (CB) and carbon nanofibers (NFs) at different ratios and at a total amount of 4 wt%. Differential scanning calorimetry shows how the introduction of both CB and NF induces a slight decrease of the glass transition temperature (Tg) of the samples. The Tg drop due to nanofiller addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Linec and Music [29] investigated the effects of the addition of silica of different shape, specific surface area and chemical structure, including crystalline and fused silica, in epoxy moulding compounds and found that T g remained almost constant. Dorigato and Pegoretti [30] introduced both carbon black (CB) and carbon nanofibers (NF) into an epoxy matrix with in situ generated silver nanoparticles and concluded that T g was "slightly reduced"; for example, for 4 wt.% nanofiller the reduction was about 5.5 • C for the CB nanofiller, but only about 2.6 • C for NF. In particular, these authors could not detect any clear trend of T g with the relative proportions of the two carbonaceous nanofillers, in agreement with their earlier observations with various other nanofilled thermosets.…”
Section: Epoxy Compositesmentioning
confidence: 99%
“…Linec and Music [29] investigated the effects of the addition of silica of different shape, specific surface area and chemical structure, including crystalline and fused silica, in epoxy moulding compounds and found that T g remained almost constant. Dorigato and Pegoretti [30] introduced both carbon black (CB) and carbon nanofibers (NF) into an epoxy matrix with in situ generated silver nanoparticles and concluded that T g was "slightly reduced"; for example, for 4 wt.% nanofiller the reduction was about 5.5 • C for the CB nanofiller, but only about 2.6 • C for NF. In particular, these authors could not detect any clear trend of T g with the relative proportions of the two carbonaceous nanofillers, in agreement with their earlier observations with various other nanofilled thermosets.…”
Section: Epoxy Compositesmentioning
confidence: 99%
“…Multiple studies have observed that T g continues to drop as nanofiller loading levels increase. 76,77 This behavior is attributed reduced crosslinking in the epoxy matrix caused by nanofillers, which dramatically alter the viscosity and undergo chemical interactions with the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…In more detail, the polymer’s thermo-responsive shape memory behavior allows it to undergo large controllable shape changes in response to a change in temperature [ 17 , 18 , 19 ]. In the case of semi-crystalline PLA, the crystalline domains act as the net points and determine the initial permanent shape of the material, while the glass transition temperature of PLA (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling PLA under loads below T g strongly reduces its mobility, thereby fixing the imposed deformation. Finally, when the polymer is heated above T g , the switching domains progressively regain their mobility, and the material returns to its original condition [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%